Surgical Reconstruction of Sole by Sural Flap among Patients with Loss of Soft Tissue at Distal Portion of Lower Limb (Journal of National Institute of Neurosciences Bangladesh, 2024)
Background: Soft tissue loss on distal one third of leg, around ankle and foot is a big problem. There are many options, but each of them has advantages and disadvantages. Sural fasciocutaneous flap is an option for this problem which has excellent results with minimum morbidity.Objective: The purpose of the present study was to role of surgical reconstruction of sole by sural flap among patients with loss of soft tissue at distal portion of lower limb.Methodology: This interventional study was carried out in the Department of Orthopedic Surgery, Ad-Din Sokhina Women’s Medical College, Jashore, Bangladesh from January 2022 to December 2022 for a period of one year. All patients with open fracture on the distal third of the tibia, exposed Achillies tendon, ankle, lateral and medial malleoli or heel reconstruction were performed by sural flap. The flap viability rate and durability of the flap at these sites were evaluated.Results: 14 patients from 14 to70years old were included in this study. We obtained excellent results with this type of flap in all the patients and success rate was considered as 100% approximately.Conclusion: With a few limitations, high success rate and collaboratively easy operative procedure; sural flap may be a good option for soft tissue loss at distal leg, ankle and foot. Journal of National Institute of Neurosciences Bangladesh, July 2023;9(2):127-131